Skrining kecacingan pada feses anak metode floatasi sentrifuge di TPA Pa’bentengan Kabupaten Gowa - Wangge, Angelina Woi; Hartati; Sulfiani (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2024)
Worms are a disease caused by intestinal  parasitic worms with a fairly high prevalence and spread throughout Indonesia. Intestinal worm infections are a chronic infection that mostly attacks children under five and elementary school age children. The aim of this research is to determine whether there are worms in children's feces at Pa'bentengan landfill using the centrifuge floatation method. The benefit of this research is to increase knowledge about worms and how important it is to maintain cleanliness in preventing worm infections. This research was conducted at Megarezky University. 20 Stool samples were taken at Pa'bentengan Gowa TPA. The research samples were then carried out using the Centrifuge Floatation method, the screening examination was continued by observing using a microscope with 10x, 40x magnification. Based on the research results, 13 samples were positive for worms and 7 samples were negatiffor worms. Having personal hygiene and a dirty living environment makes it possible for someone to be infected with worm